The Effect of Going Up and Down the Stairs to the Explosive Power of Leg Muscles in Pencak Silat Catching Snake Rolls - Weski Munandar; Windo Wiria Dinata; Endang Sepdanius; Sonya Nelson; Apri Agus; Dally Rahman; Fiky Zarya (Postgraduate, University of Mataram, 2024)
The problem in this research is the lack of explosive power of the leg muscles of pencak silat leg pencak silat catch snake roll in Lintau. For this reason, pencak silat leg pencak silat catch snake roll in Lintau needs to be trained programmatically through training principles that can be carried out both theoretically and practically in achieving maximum explosive power. There are several forms of exercise that can increase leg muscle explosive power, including an exercise program by going up and down stairs. This type of research is a quasi-experimental research. The population is the Pencak Silat College of tungkai pencak silat tangkap gulung ular in Lintau. Samples were taken by total sampling technique so that the sample amounted to 15 people. The research instrument uses a vertical jump test and the data analysis technique used is the t test hypothesis testing. As a result of research and hypothesis testing, it can be concluded that